Training strategies and the new generation - Legros, Michel (2002)
At the end of the last 20 years, a balance seemed to have been established in France between a strong emphasis on the importance of modernization for the state, even though it was accompanied by more mixed practices, and vocational training for senior staff who would be progressively inculcated with new values and translate them into teaching practices. This balance could be badly disrupted by the need for a massive and rapid renewal of a large part of the baby-boom generation teaching staff. Forced to undertake a poorly planned move towards massification, training centres could be faced with the threat of a regressive step in teaching unless they take this opportunity to commit to a renewal of training strategies. - Reproduced.
Keywords: Training